2022
DOI: 10.3390/rs14133029
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Susceptibility Mapping Using Machine Learning: A Literature Survey

Abstract: Landslide is a devastating natural disaster, causing loss of life and property. It is likely to occur more frequently due to increasing urbanization, deforestation, and climate change. Landslide susceptibility mapping is vital to safeguard life and property. This article surveys machine learning (ML) models used for landslide susceptibility mapping to understand the current trend by analyzing published articles based on the ML models, landslide causative factors (LCFs), study location, datasets, evaluation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 152 publications
0
36
0
Order By: Relevance
“…In addition, landslide susceptibility mapping techniques have been developed, including several methods: statistical, index-based, machine learning, or neural network. The machine learning technique is outstanding and accurate [9,10]. Therefore, it is important to (1) investigate the correlation between each of causative factors and detect the collinearity among the factors and (2) choose the appropriate machine learning algorithm in order to be used for landslide susceptibility modelling [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, landslide susceptibility mapping techniques have been developed, including several methods: statistical, index-based, machine learning, or neural network. The machine learning technique is outstanding and accurate [9,10]. Therefore, it is important to (1) investigate the correlation between each of causative factors and detect the collinearity among the factors and (2) choose the appropriate machine learning algorithm in order to be used for landslide susceptibility modelling [7].…”
Section: Discussionmentioning
confidence: 99%
“…There are various mathematical techniques for establishing landslide susceptibility maps that could be classified into classical statistics, index-based, machine learning, multi-criteria, and neural network [8]. In recent years, the rapidly growing and outstanding machine learning techniques in landslide evaluation have assisted in determining landslide occurrence and assessing the susceptibility of landslides [9,10]. The supervised machine learning algorithms are extensively used in landslide susceptibility research [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them also took deep learning models into consideration. Ado et al (2022) comprehensively discussed the recently developed hybrid, ensemble, and deep learning methods applied in landslide susceptibility assessment, and concluded that generally hybrid, ensemble, or deep learning models could overcome the limitations of conventional machine learning models, thus producing more accurate landslide susceptibility maps. Ma et al (2021) critically reviewed current machine learning models for landslide susceptibility investigation, and also suggested to explore the application of deep learning methods in future works.…”
Section: Introductionmentioning
confidence: 99%
“…Popular ML models used for landslide susceptibility modeling are Support Vector Machines [7,8], Artificial Neural Networks -ANN [9,10], Decision Trees [11,12], and Random Forests -RF [13,14]. More recently, hybrid/ensemble models which are combinations of single ML models and different optimization techniques are considered as better tools compared with single ML models for landslide susceptibility modeling [15]. Lucchese, De Oliveira [16] developed and applied hybrid models of ANN and RF and Bagging ensemble for landslide susceptibility modeling at the Itajaí-Açu river valley, Brazil.…”
Section: Introductionmentioning
confidence: 99%